Do Antimicrobial Proteins Contribute to Overcoming the Hidden Antifungal Crisis at the Dawn of a Post-Antibiotic Era? - László Galgóczy (Microorganisms, 2019)
The incidence of fungal infections has been grossly underestimated in the past decades as a consequence of poor identification techniques and a lack of regular epidemiologic surveys in low- and middle-income countries [...]